Induction of innate immune responses by SIV in vivo and in vitro: Differential expression and function of RIG-I and MDA5 - Go, Juliene Kimberly G. (Animo Repository, 2011)
Interferon-β induction occurs during acute simian immunodeficiency virus (SIV) infection in the brain. We have examined expression and function of cytosolic RNA sensors, retinoic acid inducible gene I (RIG-I), and melanoma differentiation-associated protein 5 (MDA5), in vivo in the brain of our consistent, accelerated SIV-macaque model and in vitro in SIV-infected macaque macrophages to identify the pathway of type I interferon (IFN) induction. MDA5 messenger RNA (mRNA) and protein were expressed at higher levels in the brain than RIG-I, with protein expression correlating with the severity of disease from 42 until 84 days post-inoculation. The siRNA experiments reveal that mRNA expression of IFN-inducible gene MxA is dependent on MDA5, but not RIG-I. Finally, we demonstrate that SIV infection leads to the production of double-stranded RNA in vivo, which may act as the MDA5 ligand. We have shown for the first time to our knowledge the functional role of MDA5 in the innate immune response to SIV infection.